Community Security Service Innovation Through a Motorcycle Security System (Sikemo) Integrated with Local Radio - Ismail; Anisa Kurniatul Azizah; Bagus Teguh Saantoso (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The Indonesian government has attempted to overcome the problem of motor vehicle theft by implementing various policies, such as increasing security patrols, installing security systems in vehicles, and providing information to the public about preventative measures. There is a need for strategies and techniques to deal with cases of theft which are very disturbing to the public. Integrated security systems for motorbikes are a promising approach in reducing crime rates. This study used descriptive qualitative method. The object of research is the security system for motor vehicle owners. Data was obtained through observation, literature study, archives and documents. Analysis through the process of identification, categorization and proposing security system innovations. SiKeMo can be an innovative solution to reduce the high rate of theft, where the existing vehicle security system is currently considered less safe. Nowadays, thieves use technology to make their actions easier. The police as a related institution need to fight increasingly sophisticated crimes by using a more sophisticated crime prevention system. By combining various security technologies, integration with wider security infrastructure, and paying attention to the psychological aspects of users, a security system can be created that is more effective and proactive in maintaining motor vehicle security.